The association of vitamin D deficiency and glucose control among diabetic patients - Mansour S Almetwazi; Ahmad O Noor; Diena M Almasri; Ioana Popovici; Tariq Alhawassi; Khalid A Alburikan; Catherine A Harrington (Saudi Pharmaceutical Journal)
Objective: To evaluate the association between the level of vitamin D and glycemic control among patients with diabetes. Research design and method: We analyzed data collected from NHANES 2003–2006. We included only non-pregnant adult diabetic persons 18 years or older. Participants who had vitamin D level less than 20 ng/ml were considered as having vitamin D deficiency. Participants were considered to have a glucose control if the HbA1c level was less than 7% [53 mmol/L]. We used student’s t test to compare the difference in HbA1c means between people with Diabetes with and without a vitamin D deficiency. We used a multivariate logistic regression model to predict the relationship between glucose control and vitamin D deficiency. We used race/ethnicity, BMI, age, gender, type of diabetic medication used, having health insurance or not, and comorbid conditions (hypertension, anemia, cholesterol, liver disease, and kidney disease) as control variables. Results: The study population included a total of 929 non-institutionalized, non-pregnant, diabetic adult persons. About 57% of patients with diabetes had a vitamin D deficiency. Blacks (non-Hispanic patients) with diabetes had the highest rate of vitamin D deficiency (79%). The unadjusted means of HbA1c were significantly different between diabetic patients with no vitamin D deficiency and those with a vitamin D deficiency (7.06% [54 mmol/L], 7.56 % [59 mmol/L], respectively, P < 0.0001). Multivariate adjustment showed a small but not significant, increase in odds (11%) of having uncontrolled diabetes in patients with a vitamin D deficiency after adjustment for other factors. Conclusion: Vitamin D deficiency is very common in patients with diabetes. We found no significant association between vitamin D level and glycemic control in patients with diabetes after adjustment for control variables. Keywords: Vitamin D deficiency, Diabetes, Glucose control, HbA1c